Perla carantana - a new species of the genus Perla (Plecoptera: Perlidae) from Austria and Slovenia - Sivec, Ignac (Natura Sloveniae, 2002)
Members of the genus Perla are the largest, and the amongst the most endangered European stonefly species. During a revisionary study of this genus, a new species was discovered at several localities in Austria and Slovenia; Perla carantana was named after Carantania, a 7th - 11th century political unit within the territories of Austria and Slovenia. Adults and larvae are nearly indistinguished on the basis of egg chorion morphology.
Keywords: Austria; Avstrija; entomologija; Plecoptera; Slovenia; Slovenija; vrbnice